FxLMS Method for Suppressing In-Wheel Switched Reluctance Motor Vertical Force Based on Vehicle Active Suspension System - Yan-yang Wang; Yi-nong Li; Wei Sun; Chao Yang; Guang-hui Xu (Journal of Control Science and Engineering)
The vibration of SRM obtains less attention for in-wheel motor applications according to the present research works. In this paper, the vertical component of SRM unbalanced radial force, which is named as SRM vertical force, is taken into account in suspension performance for in-wheel motor driven electric vehicles (IWM-EV). The analysis results suggest that SRM vertical force has a great effect on suspension performance. The direct cause for this phenomenon is that SRM vertical force is directly exerted on the wheel, which will result in great variation in tyre dynamic load and the tyre will easily jump off the ground. Furthermore, the frequency of SRM vertical force is broad which covers the suspension resonance frequencies. So it is easy to arouse suspension resonance and greatly damage suspension performance. Aiming at the new problem, FxLMS (filtered-X least mean square) controller is proposed to improve suspension performance. The FxLMS controller is based on active suspension system which can generate the controllable force to suppress the vibration caused by SRM vertical force. The conclusion shows that it is effective to take advantage of active suspensions to reduce the effect of SRM vertical force on suspension performance.